Synthesis and characterization of cordierite prepared from mixtures of Philippine kaolinite clay, talc, and other additives - Pondoc, Dionesio C. (2006)
Imported commercial kaolin clay, talc powder and light magnesium carbonate were used to synthesized cordierite body, based from the stoichiometric composition of 2MgO.2Al2O3.5SiO2, as control mixture by solid state sintering process. Philippine kaolinite clay and talc mineral rock, both from the province of Ilocos Norte were used to substitute the imported commercial materials in the following mixture ratios of 90:10, 80:20, and 70:30. Test specimens in the form of pelletized circular disks of 20 mm diameter by 2.5 mm thickness were prepared from the mixtures by powder pressing in a stainless metal mold using hydraulic press with a pressing load of 80-100 MPa. The pellets were sintered at the temperature range of 1000 degree celcius-1200 degree celcius for two and three hours in an electric furnace. The effects of mixture ratio, sintering temperature and sintering time to the bulk density, apparent porosity, linear shrinkage and compressive strength of the synthetic cordierite were determined by conducting full factorial experiment. Results in the characterization of synthesized cordierite body using x-ray diffraction (XRD) analysis revealed the formation of u-cordierite and x-cordierite in all test specimens of the three mixture ratios sintered at 1000 degree celcius within the sintering time of two and three hours. At 1100 degree celcius, the diffraction peaks detected were mostly formation of a x-cordierite as the major crystalline phase with the presence of small amount of u-cordierite and spinel. SEM characterization analyses show that the microstructures were transformed from uniformly euhedral particles (size range of 1-10 um) to spherical particles as the sintering temperature increases from 1000 degree celcius to 1200 degree celcius. Open pores between spherical particles can also be distinguished.